1996
DOI: 10.3758/bf03213093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-pass and low-pass spatial filtering on face identification

Abstract: If face images are degraded by block averaging, there is a nonlinear decline in recognition accuracy as block size increases, suggesting that identification requires a critical minimum range of object spatial frequencies. The identification of faces was measured with equivalent Fourier low-pass filtering and block averaging preserving the same information and with high-pass transformations. In Experiment 1, accuracy declined and response time increased in a significant nonlinear manner in all cases as the spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
219
4
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(252 citation statements)
references
References 27 publications
(61 reference statements)
24
219
4
3
Order By: Relevance
“…Costen et al (1996) have investigated the effect of high-pass and low-pass filtering on face images in isolation, and Parker, Lishman and Huges (1996) have investigated the effect of high-pass and low-pass filtering of face and object images used as 100 ms cues for a same/different task. Their results indicate that relevant high-pass filtered images cue object processing better than low-pass filtered images, but the two types of filtering cue face processing equally well.…”
Section: Discussion Of Model II Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Costen et al (1996) have investigated the effect of high-pass and low-pass filtering on face images in isolation, and Parker, Lishman and Huges (1996) have investigated the effect of high-pass and low-pass filtering of face and object images used as 100 ms cues for a same/different task. Their results indicate that relevant high-pass filtered images cue object processing better than low-pass filtered images, but the two types of filtering cue face processing equally well.…”
Section: Discussion Of Model II Resultsmentioning
confidence: 99%
“…Costen, Parker and Craw (1996) showed that although both high-pass and low-pass image filtering decrease face recognition accuracy, high-pass filtering degrades identification accuracy more quickly than low-pass filtering. Also, Schyns and Oliva (1999) have shown that learning the identity of a set of faces later biases subjects' perception toward low spatial frequency information.…”
Section: Developmental Data and A Possible Low Spatial Frequency Biasmentioning
confidence: 99%
“…They have also confirmed the importance of the midband of spatial frequencies (8-25 cycles per face), which may provide the optimal information for judgments of face identity (see Costen, Parker, & Craw, 1994, 1996Nasanen, 1999;Ruiz-Soler & Beltran, 2006). Crucially, however, no reverse correlation study (to the best of our knowledge) has explored the visual information driving familiarity decisions (i.e., without an explicit naming component).…”
mentioning
confidence: 77%
“…Bachmann (1991), using a delayed match-to-sample task, found a rapid decrease in accuracy as coarse-quantized face images were reduced in resolution from 18 pixels per face width to 15. In related experiments, Costen et al (1994Costen et al ( , 1996, using a similar method to Bachmann's, found abrupt drop-offs in performance as faces were low-pass filtered at cutoffs less than 8 cycles per face or high-pass filtered at greater than 16 cycles per face. In experiments comparing human delayed match-to-sample performance with that of an ideal observer algorithm, Nasanen (1999) found a reduction in the efficiency function of participants when frequencies around 8 -13 cycles per face were masked by noise.…”
mentioning
confidence: 96%
“…The researchers suggested that this lack of a critical band effect in their data was based on the contributions of overlapping and interfering frequencies. They pointed out that studies such as those of Costen et al (1994Costen et al ( , 1996 used full-bandwidth pictures at learning, meaning that there was a large range of frequencies in the learned image that were not present in the tested image. These frequency elements may have interfered with recognition, as they would have found no equivalents in the tested images.…”
mentioning
confidence: 99%